Vocabulario marinero de Costa Rica - Korneliussen, Randi (2004)
The present article describes and analyses the vocabulary used by fishermen and sailors in Costa Rica, such as tasks related to the sea and the act of fishing. The linguistic material was gathered along the Caribbean and Pacific coasts by means of a geolinguistic field work. In this article, a glossary of the recompiled vocabulary is included.